Analisis Efisiensi Kinerja Bank Syariah Menggunakan Data Envelopment Analysis dan Sharia Maqashid Index - Ilham Hibatullah; Trisiliadi Supriyatno; Irfan Syauqi Beik (Banque Syar'i: Jurnal llmiah Perbankan Syariah, 2023)
This study aims to measure the efficiency of the performance of Islamic banks in Indonesia, Malaysia, Saudi Arabia, Pakistan, United Arab Emirates and Bahrain using the Data Envelopment approach Analysis (DEA) and Sharia Maqashid Index (SMI).This study uses a combination research method. In the first stage, quantitative research is used to measure the efficiency of the performance of 4 Islamic banks from 6 countries in 2018-2020 with the Data Envelopment Analysis (DEA) and Sharia Maqashid Index (SMI) approaches. In the second stage, qualitative methods are used to compare the results of performance measurement along with the appropriate approach to measure the performance of Islamic banks. The results of this study indicate that in the DEA approach, only 2 Islamic banks consistently have perfect efficiency scores (1 or 100%) namely BRI Syariah (Indonesia) and Kuwait House Finance (Bahrain). As for SMI, the 3 Islamic banks with the highest scores were Bank Muamalat Indonesia (39,020), Al Bilad Bank (36,938) and Alinma Bank (35,335) Saudi Arabia. Performance measurement using these two approaches is very well used to assess the performance of Islamic banks from the aspect of profitability and Sharia Maqashid.